Vicente Aleixandre and the Solidarity of the Cosmos - Carl W. Cobb (Studies in 20th & 21st Century Literature, 1977)
Vicente Aleixandre and the Solidarity of the Cosmos
Keywords: Vicente Aleixandre; poetry; religion